2015
DOI: 10.1021/jf504254q
|View full text |Cite|
|
Sign up to set email alerts
|

UHPLC-MS/MS Determination of Ochratoxin A and Fumonisins in Coffee Using QuEChERS Extraction Combined with Mixed-Mode SPE Purification

Abstract: A method was developed for simultaneous determination of the mycotoxins: ochratoxin A (OTA) and fumonisins B2 (FB2), B4 (FB4), and B6 (FB6) in green, roasted, and instant coffee. Extraction was performed by QuEChERS (quick, easy, cheap, effective, rugged, and safe) under acidic conditions followed by mixed-mode reversed phase-anion exchange solid phase extraction. OTA and FB2 were detected at levels down to 0.5 and 2 μg/kg by UHPLC-MS/MS and quantitated via isotope dilution using U-(13)C-labeled FB2 and OTA as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
3
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(31 citation statements)
references
References 35 publications
1
24
3
2
Order By: Relevance
“…It was suggested that the amine group of the mycotoxins could bound to the free silanol groups on the glass surface of the used test tubes. The loss level was lower than the results reported previously, which was up to 75% (Nielsen et al 2015). Therefore, we selected the method of dilution of the MSPE eluate instead of evaporation.…”
Section: Characterisation Of Magnetic Nanoparticles (Mnps)mentioning
confidence: 71%
“…It was suggested that the amine group of the mycotoxins could bound to the free silanol groups on the glass surface of the used test tubes. The loss level was lower than the results reported previously, which was up to 75% (Nielsen et al 2015). Therefore, we selected the method of dilution of the MSPE eluate instead of evaporation.…”
Section: Characterisation Of Magnetic Nanoparticles (Mnps)mentioning
confidence: 71%
“…Although satisfactory analytical performances were reported in terms of recoveries and repeatability, application of the proposed method to naturally contaminated samples was not investigated. Nielsen et al (2015) reported on the development of a LC-MS/MS method for simultaneous determination of OTA and fumonisins B 2 , B 4 (FB 4 ), and B 6 (FB 6 ) in green, roasted, and instant coffee. To maximise recoveries of these toxins containing acidic functional groups, extraction was performed by an acidified water/methanol mixture followed by mixed-mode reversed phase-anion exchange SPE (Oasis MAX® cartridges).…”
Section: Multi-mycotoxin Lc-ms(/ms) Methodsmentioning
confidence: 99%
“…Extraction using QuEChERS-type procedures have previously been applied to fumonisins in various commodities. Recently, the technique, in combination with mixed-mode SPE was used to isolate FB 2 , FB 4 , FB 6 , and OTA from green, roasted, or instant coffee (Nielsen et al, 2015). Using an isotopic internal standard, the LOD of the method was 2 µg/kg.…”
Section: Fumonisinsmentioning
confidence: 99%
“…Acid catalyzed reactions can be especially problematic when evaporating organic extracts, since the lower volatility of acids such as formic and acetic acids will result in upconcentration when using volatile solvents like EtOAc and DCM, especially in the presence of residual water. Examples we have observed include; up to 50% loss of patulin during evaporation from EtOAc ( Boonzaaijer et al, 2005 ); loss of trichothecenes prior to derivatization for GC-MS analysis ( Langseth and Rundberget, 1998 ); up to 80% loss of fumonisins due to binding to the silanol groups of non-derivatized glass with up to 80% lost ( Nielsen et al, 2015 ). We have used a fast extraction procedure to minimize the risk of studying artifact peaks, this procedure involves extraction into acetonitrile-water (1:1; in a ultrasonication bath or a beadbeater for circa 10 min), followed by centrifugation and subsequent transfer of the centrifugate directly to an auto-sampler compatible vial for analysis ( Mogensen et al, 2011 ).…”
Section: The Importance Of Sample Preparationmentioning
confidence: 99%